Effect of Receiver Holes on Flow and Heat Transfer Characteristics in A Radial Pre-swirl System: A LES Study - D. Wang; C. Song; C. Qiu; W. Wang; Y. Xu; P. I. Mihailovich (Journal of Applied Fluid Mechanics)
As a necessary component of a turboshaft engine, optimizing components in the radial pre-swirl system is critical for improving turbine performance. The aim of this study was to investigate the impact of receiver holes on the flow and heat transfer characteristics of various components in the pre-swirl system. Large-eddy simulations were used to demonstrate the phenomenon that the different receiver hole tangential angles have a significant influence on the performance of the radial pre-swirl system. In addition, a mathematical model was developed to predict the relative total pressure and temperature inside the co-rotating cavity. It is observed that the relative total pressure of computational model with receiver hole tangential angle equals to 15° is 21.88% and 18.54% larger than that of the computational model with receiver hole tangential angles equals to 0° and 7.5°as a result of the increase in swirl ratio. A larger swirl ratio resulted in a stronger centrifugal supercharging effect and jet acceleration effect. Furthermore, the Nusselt number and the field synergy angle exhibited an upward and downward trend, respectively. Subsequently, an investigation of unsteady characteristics designed to reveal the vortex state inside the co-rotating cavity was carried out. The mathematical model’s prediction result matched the LES result closely, demonstrating its practical significance.